PERANCANGAN SISTEM INFORMASI SIRP UNTUK MENCATAT RIWAYAT PERJALANAN MASYARAKAT SELAMA PERIODE PANDEMI (Studi Kasus: Kecamatan IV Koto Aur Malintang) - Darmansah Darmansah Darmansah (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
Starting in early 2020, the Corona Virus 2019 or Covid-19 has become an epidemic that has spread to almost all countries in the world including Indonesia. many are caused by the corona virus, ranging from health, education to economic impacts. A way is needed to increase awareness by making an information recording the travel history of the community during the pandemic in order to help population data to prevent the transmission of the corona virus. The sub-district government of IV Koto Aur Malintang is one of the governments in the province of West Sumatra that manually collects data on the travel history of the community during the pandemic period or has not maximized computerization. This certainly makes the sub-district government in recording and administering public data entering and leaving the environment ineffective and lacking information. For this reason, as a way to assist the central government in reducing the rate of transmission and controlling the movement of people entering or leaving the IV Koto Aur Malintang sub-district government, it is necessary to build a website-based SIRP (Travel History Information System) information system. The SIRP (Travel History Information System) is able to data the people who enter and leave the government of the IV Koto Aur Malintang sub-district during the pandemic. In designing the SIRP (Travel History Information System), researchers used UML (Unified Modeling Language) modeling. UML is used to facilitate researchers in designing the system to be made. The method that researchers use in this research is the prototyping method. With the construction of the Pandemic Travel History Information System (SIRP) at this time, it is hoped that the sub-district government of IV Koto Aur Malintang can see where and who is in and out of the area and then also provide clear data and information to the community regarding how many people are currently under surveillance. (ODP) and people without symptoms (OTG). In addition, the Travel History Information System (SIRP) certainly makes it very easy for the government to reduce the rate of transmission of the Corona virus in West Sumatra, especially in Sub-district IV Koto Aur Malintang, because it can easily record people who enter and leave the area.